Accelerated Accumulation of Multimorbidity After Bilateral Oophorectomy: A Population-Based Cohort Study - Rocca, Walter A. (Mayo Clin Proc, 2016)
OBJECTIVE: To study the association between bilateral oophorectomy and the rate of accumulation of multimorbidity. PATIENTS AND METHODS: In this historical cohort study, the Rochester Epidemiology Project records-linkage system was used to identify all premenopausal women who underwent bilateral oophorectomy before age 50 years between January 1, 1988, and December 31, 2007, in Olmsted County, Minnesota. Each woman was randomly matched to a referent woman born in the same year (± 1 year) who had not undergone bilateral oophorectomy. We studied the rate of accumulation of 18 common chronic conditions over a median of approximately 14 years of follow-up. RESULTS: Although women who underwent bilateral oophorectomy already had a higher multimorbidity burden at the time of oophorectomy, they also experienced a significantly increased risk of subsequent multimorbidity (P=.XX). After adjustments for 18 chronic conditions present at baseline, race/ethnicity, education, body mass index, smoking, age at baseline, and calendar year at baseline, women who underwent oophorectomy before age 46 years experienced an increased risk of depression, hyperlipidemia, cardiac arrhythmias, coronary artery disease, arthritis, asthma, chronic obstructive pulmonary disease, and osteoporosis. In addition, they experienced an accelerated rate of accumulation of the 18 chronic conditions considered together (hazard ratio, 1.22; 95% CI, 1.14–1.31; P<.001). Several of these associations were reduced in women who received estrogen therapy. CONCLUSION: Bilateral oophorectomy is associated with a higher risk of multimorbidity, even after adjustment for conditions present at baseline and for several possible confounders. However, several of these associations were reduced in women who received estrogen therapy.